PENERAPAN MEDIA ULAR TANGGA BERKARTU PERTANYAAN UNTUK MENINGKATKAN KEAKTIFAN DAN HASIL BELAJAR IPAS SISWA SD - Jesicha Kurnia Non; Herry Sanoto (ACADEMIA: Jurnal Inovasi Riset Akademik, 2026)
ABSTRACT This study was motivated by the low levels of learning participation and science learning outcomes among fourth-grade students at SDN Kadirejo 02, which were caused by the dominance of lecture-based teaching methods and the limited use of engaging learning media. The study aimed to describe the implementation of a snakes-and-ladders learning medium integrated with question cards and to improve students’ learning participation and science learning outcomes. This research employed the Classroom Action Research (CAR) method using the Kemmis and McTaggart model, conducted in two cycles consisting of planning, action, observation, and reflection stages. The participants were 25 fourth-grade students of SDN Kadirejo 02, Pabelan District, Semarang Regency. Data were collected through learning participation observation sheets and learning achievement tests administered at the end of each cycle. The results showed improvements in both students’ learning participation and learning outcomes across the cycles. The average learning outcome score increased from 57.60 in the pre-cycle to 71.60 in Cycle I and 86.80 in Cycle II. Classical learning mastery also improved from 0% in the pre-cycle to 52% in Cycle I and reached 100% in Cycle II. In addition, students’ learning participation increased from the “fair” category (55.60%) to the “good” category (81.40%). These findings indicate that the use of a snakes-and-ladders learning medium integrated with question cards can enhance students’ learning participation and science learning outcomes on the topic of States of Matter and Their Changes. ABSTRAK Penelitian ini dilatarbelakangi oleh rendahnya keaktifan dan hasil belajar IPAS siswa kelas IV SDN Kadirejo 02 yang disebabkan oleh penggunaan metode pembelajaran yang masih didominasi ceramah dan kurangnya media pembelajaran yang menarik. Penelitian ini bertujuan untuk mendeskripsikan penerapan media pembelajaran ular tangga berbasis kartu pertanyaan serta meningkatkan keaktifan dan hasil belajar IPAS siswa. Penelitian menggunakan metode Penelitian Tindakan Kelas (PTK) model Kemmis dan McTaggart yang dilaksanakan dalam dua siklus, meliputi tahap perencanaan, tindakan, observasi, dan refleksi. Subjek penelitian adalah 25 siswa kelas IV SDN Kadirejo 02, Kecamatan Pabelan, Kabupaten Semarang. Data dikumpulkan melalui lembar observasi keaktifan belajar dan tes evaluasi hasil belajar pada setiap akhir siklus. Hasil penelitian menunjukkan adanya peningkatan keaktifan dan hasil belajar siswa pada setiap siklus. Rata-rata hasil belajar meningkat dari 57,60 pada pra siklus menjadi 71,60 pada siklus I dan 86,80 pada siklus II. Ketuntasan belajar klasikal juga meningkat dari 0% pada pra siklus menjadi 52% pada siklus I dan mencapai 100% pada siklus II. Selain itu, keaktifan belajar siswa meningkat dari kategori cukup (55,60%) menjadi kategori baik (81,40%). Temuan ini menunjukkan bahwa penggunaan media ular tangga berbasis kartu pertanyaan dapat meningkatkan keaktifan dan hasil belajar IPAS siswa pada materi Wujud Zat dan Perubahannya.